Believing Is Seeing - Principe, Gabrielle F.; Kanaya, Tomoe; Ceci, Stephen J.; Singh, Mona (Psychological Science, 2006)
This study examined how an erroneous rumor circulated among preschoolers can influence their memory. One fourth of the children overheard a rumor from an adult conversation in which it was alleged that an event the children had not experienced themselves had occurred. A second fourth were the classmates of those who overheard the rumor. A third group had no exposure to the rumor. The remaining children actually experienced the event suggested by the rumor. One week later, the children were interviewed in either a neutral or a suggestive manner. Results from a second interview after a 2-week delay revealed that under both interview conditions, children who overheard the rumor, either from the adult conversation or during naturally occurring interactions with classmates, were as likely to report experiencing the rumored but nonexperienced event as were those who actually experienced it. Most reports of the rumored but nonexperienced event were in children's free recall and were accompanied by high levels of fictitious elaboration.